(untitled) (GEOmedia, 2024)
On the occasion of the 80th anniversary of the destruction of the Abbey of Montecassino, and of the city of Cassino, we remember here these tragic events that affected both culture and civil society, retracing them through the WWII aerial photographs preserved in Aerofototeca Nazionale in the Mediterranean Allied Photographic Reconnaissance Wing (MAPRW) collection. They were taken by British Royal Air Force (RAF) reconnaissance aircraft on the morning of March 15th, 1944, during the Third Battle of Montecassino. One month after the Second Battle (February 15th, 1944) - in which military strategies bomber and completely destroyed the sacred Abbey founded by Saint Benedict in 529 A.D. - nothing can be seen of the city, as it is covered by ground artillery smoke, while the Abbey is in ruins. Together with many others kept in the archives of the Aerofototeca Nazionale in Rome, these outstanding images show one of the more salient moments of Italian national history.